Communication in Science teaching: reflections from a bibliographic review in the Brazilian context (Research, Society and Development, 2021)
The ongoing change regarding the intensification of the use of  media by society and the forms of access and speed with which information flows, have significantly influenced the teaching and learning processes that take place inside and outside the school. Therefore, the objective of this research was to analyze how the Nature Science teaching area has been dealing with the different means and resources of communication in the Brazilian context. To this end, five national journals in the area were chosen, from which 116 articles were selected in the period between 2010 and 2016. For data analysis, categories were constructed using Discursive Textual Analysis. There were identified descriptive works, works with practical application in teaching, but with little student involvement, and works with a more democratic perspective of participation and protagonism. Communication was present in all described educational processes. The use of digital resources prevailed, a trend that deserves to be closely monitored, noting the need for educators to organize and plan teaching and learning processes in a bold and creative way, in the search for the protagonism of students and the thought on the use of resources which must be carried out with critical reading and questioning.